A retrospective analysis of High-Dose Interleukin-2 (HD IL-2) following Ipilimumab in metastatic melanoma. Issue 1 (December 2016) - Buchbinder, Elizabeth; Gunturi, Anasuya; Perritt, Jessica; Dutcher, Janice; Aung, Sandra; Kaufman, Howard; Ernstoff, Marc; Miletello, Girald; Curti, Brendan; Daniels, Gregory; Patel, Sapna; Kirkwood, John; et al.
Abstract Background High dose interleukin-2 (HD IL-2) can induce durable responses in a subset of patients leading to long-term survival. Immune checkpoint blockade (ICB) has demonstrated similarly durable responses in a larger proportion of patients. However, not all patients respond to immune checkpoint blockade and subsequent therapeutic options need to be explored. Methods The PROCLAIM database was queried for patients with metastatic melanoma who had received HD IL-2 after treatment with ipilimumab or without prior ICB. Patient characteristics, toxicity and efficacy were analyzed. Results A total of 52 metastatic melanoma patients were treated with high dose IL-2 after ipilimumab and 276 patients were treated with high dose IL-2 without prior ICB. The overall response rate in the prior ipilimumab group was 21 % as compared to 12 % in the group that had not received prior ipilimumab. The median overall survival, measured from the initiation of HD IL-2 therapy, was 19.3 months in the prior ipilimumab group and 19.4 months in the no prior ICB group. Toxicities observed on HD IL-2 were relatively equivalent between the groups although there were cases of CTLA4 antibody-induced colitis reported after HD IL-2 treatment and a CTLA4 antibody-induced colitis related death. Conclusion In this retrospective analysis HD IL-2 therapy displayed antitumor activity in melanoma patients who progressed following treatment with ipilimumab. Most HD IL-2 toxicity was not worsened by prior ipilimumab therapy except for one treatment related death from colitis. Care should be taken to avoid reactivation of CTLA4 antibody-induced colitis.